The influence of telemedicine in primary healthcare on diabetes mellitus control and treatment adherence in Riyadh region - Ziyad S Almalki; Mohammad T. Imam; Nehad J. Ahmed; Rahaf K. Ghanem; Taghreed S.Alanazi; Syeda Juweria; Taraf S .Alanazi; Raghad B. Alqadhibi; Shadan Alsaleh; Fadah H. Hasino; Amirh saad Alsffar; Abdulaziz I Alzarea; et al. (Elsevier, 2024)
Several studies have found that telemedicine has the potential to enhance the outcomes of patients with diabetes. This study aimed to determine the impact of telemedicine on the clinical outcomes of patients with type 2 diabetes mellitus (T2DM) in Saudi Arabia. We conducted a cross-sectional study among T2DM patients in selected primary healthcare centers in Riyadh, Saudi Arabia, from March 1, 2023, to August 20, 2023. We looked at how telemedicine affected HbA1c control, adherence, the number of diabetic complications, and polypharmacy using adjusted multivariable logistic regression models. Among the 583 patients, 140 (24.05 %) received care via telemedicine, while 442 (75.95 %) received in-person care. Patients who utilized telemedicine had significantly better glycemic control than those who received in-person care only (AOR = 5.123, 95 % CI = 3.107-8.447). Telemedicine also showed positive effects on treatment adherence (AOR = 2.552, 95 % CI = 1.6284-4.2414). Telemedicine can effectively reduce diabetic complications (AOR = 0.277, 95 % CI = 0.134-0.571). Regarding polypharmacy, patients with telemedicine use were less likely to report polypharmacy (AOR = 0.559, 95 % CI = 0.361-0.866). Telemedicine is considered one of the factors that improve HbA1c management and might increase therapeutic adherence and reduce diabetic complications and polypharmacy.